(untitled) (Colombia Medica, 2006)
Background: Cystic fibrosis (CF) is the most frequent autosomal recessive disorder in the Caucasian population with an incidence of 1 in 2,500 newborns. More than 1,300 mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) gene that causes CF have been described. However, mutation F508del is the most common mutation in different populations around the world. Objective: To develop a fast, reliable and low-cost technique to screen carriers and affected individuals for the F508del mutation. This kind of analysis will have an impact on genetic counselling to decrease the incidence of new cases, in the early diagnosis and instauration of appropriate treatment to decrease morbidity and mortality associated to CF in Colombia. Methods: The reliability of the PCR-heteroduplex by grouping technique by analysis of 400 blood spot samples from asymptomatic CF patients was defined. Results: Using PCR-heteroduplex by grouping technique 100% efficiency, reproducibility and specificity and 92%sensitivity were found. Conclusions: The sensitivity and reproducibility of the PCR-heteroduplex by grouping technique up to pooling of 10 samples were demonstrated. This kind of analysis could be used in heterozygotes and affected screening programs.